PLIO-QUATERNARY SEGMENTATION OF THE SOUTH TYRRHENIAN FOREARC BASIN - Guarnieri P. (My University, 2006)
The structural elements constituting the forearc basin of the Calabrian Arc–Sicily orogenic system are recognizable on land and in the Tyrrhenian offshore. The Plio–Pleistocene retreat of the Ionian subduction hinge, coeval with the roll-back of the Africa continental crust, leads to segmentation of the forearc basin and southeastward migration of the Calabrian Arc due to its higher degree of mobility compared to Sicily, where, on the contrary, continental collision takes place. The analysis of geological data collected in three areas of the orogenic belt and the integration with offshore geophysical data show evidence of two phases of subduction hinge retreat: (1) Late Pliocene–Early Pleistocene southeastward migration accompanied by the development of N120°E trending tear-faults and NE–SW-trending extensional systems, (2) Middle–Late Pleistocene SSE-ward migration with development of NNW–SSE-trending tear-faults and N70°E-trending collapse systems. The data presented here provide an innovative framework for the interpretation of this most seismically active area of the Mediterranean. In particular, in the Messina Strait area, the more recent N70°E lineaments could be associated with the faults that generated the 1783 Calabria earthquake and are coherent with the focal mechanism of the 1908 Messina earthquake, confirmed also by the analysis of frequency diagrams of the elongation directions of the isoseists.
Keywords: PLIO-QUATERNARY; SOUTH TYRRHENIAN; FOREARC BASIN; CALABRIAN ARC; IONIAN SUBDUCTION; MESSINA STRAIT; Pleistocene; Pliocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен